Synthesis of Nanosilver Coated Sand Using Plant Extracts. (2016) - Farhana, M.; Meera, V.
Abstract: Silver nanoparticles are gaining more attention now-a-days in environmental application due to their high surface area to volume ration and antimicrobial property. The commonly used methods for silver nanoparticle synthesis are the physical and chemical methods. The drawback of chemical and physical methods is that the synthesis is expensive and also involves the use of toxic, hazardous chemicals, which may pose potential environmental and biological risks. The biological method provides a feasible alternative for this problem. The major biological systems involved are bacteria, fungi, and plant extracts. Plants are better synthesizers as compared to the other biological methods. Due to the practical difficulties of silver nanoparticles for water treatment, these nanoparticles must be coated onto some supports. From energy dispersive spectroscopy, all the nanosilver coated sand showed 0.91%-1.35% of silver on coated sand whereas silver coated sand showed only 0.39% of silver on sand. The size of nanosilver coated sand synthesised using papaya fruit extract was found to be about 43.8 nm by X- ray diffraction spectrum. The Scanning electron microscopic image of nanosilver coated sand synthesised using papaya fruit extract showed nearly spherical shape and discontinuous coating. This study focuses on the preparation of silver nanoparticles coated on sand using different plant extracts.